Gelam honey has a protective effect against lipopolysaccharide (LPS)-induced organ failure - Kassim, M.; Mansor, M.; Al-Abd, N.; Yusoff, K.M. (2012)
Gelam honey exerts anti-inflammatory and antioxidant activities and is thought to have potent effects in reducing infections and healing wounds. The aim of this study was to investigate the effects of intravenously-injected Gelam honey in protecting organs from lethal doses of lipopolysaccharide (LPS). Six groups of rabbits (N = 6) were used in this study. Two groups acted as controls and received only saline and no LPS injections. For the test groups, 1 mL honey (500 mg/kg in saline) was intravenously injected into two groups (treated), while saline (1 mL) was injected into the other two groups (untreated); after 1 h, all four test groups were intravenously-injected with LPS (0.5 mg/kg). Eight hours after the LPS injection, blood and organs were collected from three groups (one from each treatment stream) and blood parameters were measured and biochemical tests, histopathology, and myeloperoxidase assessment were performed. For survival rate tests, rabbits from the remaining three groups were monitored over a 2-week period. Treatment with honey showed protective effects on organs through the improvement of organ blood parameters, reduced infiltration of neutrophils, and decreased myeloperoxidase activity. Honey-treated rabbits also showed reduced mortality after LPS injection compared with untreated rabbits. Honey may have a therapeutic effect in protecting organs during inflammatory diseases. Â© 2012 by the authors; licensee MDPI, Basel, Switzerland.